Fargesia sapaensis (Poaceae, Bambusoideae), a new bamboo species from Lao Cai, Vietnam - Zhang, You-Yuan; Tong, Yi-Hua; Ni, Jing-Bo; Vu, Tien-Chinh; Xia, Nian-He (Phytotaxa, 2020)
Fargesia sapaensis N.H.Xia & Y.Y.Zhang, a new species from Lao Cai, Vietnam, is described and illustrated. The new species is similar to F. dracocephala T.P.Yi and F. fansipanensis T.Q.Nguyen, but differs from the former mainly in its mid-culm complement of 3–7 branches at each node, auricles of culm sheaths absent, 2‒6 florets per spikelet, 7‒10 mm long first glume and 2‒3 mm long lodicules, and from the latter by its culm sheaths shorter than culm internodes, 3–4 leaves per ultimate branch, and a mid-culm complement of 3–7 branches at each node.